PENERAPAN BREAK EVEN POINT PADA PABRIK RICE PROCESSING COMPLEX (RPC) ANABANUA KABUPATEN WAJO - Sukiman Sukiman; Hasanuddin Hasanuddin (Al-Buhuts, 2016)
This research aimed to provide an illustration of the production amount in order to achieve the value of the break even point.Analysis method used was descriptive-quantitative. The data were analysed using the Break Even Point analysis.The research results revealed that; (1) RPC as a rental service provider of the rice mill of Rp. 250 per kg which has the value of the break even points of production of 27.373.889 kg per year. Its exceed the maximum production capacity of the machine of 25,920,000 kg per year; (2) RPC was not able to reach the value of the break even point of production was only cooperated with one business partner as the use of rice milling services with the highest capacity of supply of 520,660 kg per year